Optimization of NURBS Parameters for Computing Kinematic Characteristics of the Cam Oscillating Roller Follower - Nguyen, Van Trang; Nguyen, Thi Thanh Nga (Engineering, Technology & Applied Science Research, 2025)
This paper presented an approach for the design and optimization of cam mechanisms with oscillating roller followers using Non-Uniform Rational B-Spline (NURBS) curves. The follower’s motion and its kinematic parameters, including velocity, accelerations, and jerk were expressed through a NURBS transfer function. To optimize the problem, the maximum values of acceleration and jerk were minimized. Additionally, a simulated annealing algorithm was developed to determine the optimal NURBS parameters. An example in cutting machines was used to evaluate this method individually and comparatively with other two methods (B-Spline and polynomial). The results demonstrated that the proposed method provided flexibility in using the transfer function for the follower in order to improve the kinematic characteristics of the cam systems. This research not only raises the significance in the design of cam oscillating roller follower, but also hands out the potential application for other related cam systems.